Pengaruh Literasi Keuangan, Pendidikan Keuangan di Keluarga, Uang Saku terhadap Perilaku Pengelolaan Keuangan dengan Financial Self-Efficacy sebagai Variabel Intervening - Novi Ratna Sari; Agung Listiadi (Jurnal Pendidikan Akuntansi (JPAK), 2021)
This study aims to analyze the effect of financial literacy, financial education in the family, and pocket money on financial management behavior through financial self-efficacy, either directly or indirectly. This type of research is quantitative research. The population in this research is active students of the Faculty of Economics and Business, State University of Surabaya. The sampling technique used purposive sampling and obtained 170 students as respondents. The data collection method used a questionnaire. The data analysis technique used instrument test, classical assumption test, multiple linear regression analysis, path analysis with SPSS 24. The results of the study were as follows: (1) financial literacy has no effect on financial management behavior either directly or through financial self-efficacy (2) financial education in the family has a positive effect on financial management behavior both directly and through financial self-efficacy (3) pocket money has an effect on financial management behavior both directly and through financial self-efficacy (4) financial self-efficacy has a significant positive effect on financial management behavior.